Rotten Ralph feels rotten - Gantos, Jack.; Rubel, Nicole (New York : Farrar Straus Giroux, 2004)
Rotten Ralph comes to appreciate Sarah's healthy cat food after he gets sick from eating out of trash cans.
Booklist starred
Horn Book
2.5
K-3
Keywords: Cats -- Fiction; Food habits -- Fiction; Cats -- Fiction; Eating customs -- Fiction